Systematic design and implementation of a semantic assistance system for aero-engine design and manufacturing. (7th January 2022) - Gogineni, Sonika; Brünnhäußer, Jörg; Lindow, Kai; Konietzko, Erik Paul; Stark, Rainer; Nickel, Jonas; Witte, Heiko
Data in organisations is often spread across various Information and Communication Technology (ICT) systems, leading to redundancies, lack of overview and time wasted searching for information while carrying out daily activities. This paper focuses on addressing these problems for an aerospace company by using semantic technologies to design and develop an assistance system using existing infrastructure. In the aero-engine industry, complex data systems for design, configuration, manufacturing and service data are common. Additionally, unstructured data and information from numerous sources become available during the product's life cycle. In this paper, a systematic approach is followed to design a system, which integrates data silos by using a common ontology. This paper highlights the problems being addressed, the approach selected to develop the system, along with the implementation of two use cases to support user activities in an aerospace company.